2015
DOI: 10.1086/682950
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Sex Allocation in the Parasitoid WaspNasonia vitripennis

Abstract: Dryad data: http://dx.doi.org/10.5061/dryad.15nj0. abstract:The role of epigenetics in the control and evolution of behavior is being increasingly recognized. Here we test whether DNA methylation influences patterns of adaptive sex allocation in the parasitoid wasp Nasonia vitripennis. Female N. vitripennis allocate offspring sex broadly in line with local mate competition (LMC) theory. However, recent theory has highlighted how genomic conflict may influence sex allocation under LMC, conflict that requires pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…This subtle shift is as predicted by genomic conflict over sex allocation theory, which 121 requires some form of genomic imprinting (Wild and West 2008). Assuming that DNA methylation is 122 the mechanism by which parent-of-origin allelic information is carried in Nasonia (although see Wang 123 et al 2016), our data therefore provided the first (albeit indirect) evidence for genomic conflict 124 influencing sex allocation (Cook et al 2015a). Although patterns of methylation differ among eukaryotes, the epigenetic modification itself is 140 chemically identical.…”
Section: Introduction 52mentioning
confidence: 57%
“…This subtle shift is as predicted by genomic conflict over sex allocation theory, which 121 requires some form of genomic imprinting (Wild and West 2008). Assuming that DNA methylation is 122 the mechanism by which parent-of-origin allelic information is carried in Nasonia (although see Wang 123 et al 2016), our data therefore provided the first (albeit indirect) evidence for genomic conflict 124 influencing sex allocation (Cook et al 2015a). Although patterns of methylation differ among eukaryotes, the epigenetic modification itself is 140 chemically identical.…”
Section: Introduction 52mentioning
confidence: 57%
“…However, research into the mechanisms involved in sex allocation in N. vitripennis is much less advanced, both in terms of the genetic basis of sex ratio and in terms of the underlying neuroscience. Quantitative genetic studies have revealed QTL associated with sex ratio variation (Pannebakker et al, 2011), transcriptomics studies have investigated gene expression patterns associated with sex allocation (Cook et al, 2015a), and a role for epigenetics, specifically DNA methylation, has also been inferred (Cook et al, 2015b). However, we still know virtually nothing of the neural substrates of sex allocation.…”
Section: Introductionmentioning
confidence: 99%
“…It has often been suggested that genomic imprinting is absent outwith mammals and flowering plants, largely on account of lack of evidence from model organisms such as D. melanogaster (Chapman 2006;Spencer and Clark 2014;Yan et al 2014). Nevertheless, there is growing direct and indirect evidence of extensive methylation, and even genomic imprinting, in other insects, such as hymenoptera (Wang et al 2006;Kronforst et al 2008;Kucharski et al 2008;Herb et al 2012;Amarasinghe et al 2014;Oldroyd et al 2013;Yan et al 2014Yan et al , 2015Cook et al 2015;Galbraith et al 2016;Remnant et al 2016). Such taxa provide excellent opportunities for developing new theoretical and empirical avenues of genomic imprinting research (Queller 2003;Rautiala and Gardner 2016).…”
Section: Discussionmentioning
confidence: 99%